Method for preparing single crystal ternary material, single crystal ternary material and lithium ion battery
The preparation of single-crystal ternary materials through prefiring and crushing treatment solves the problems of poor adaptability of the precursor and difficult to control the sintering temperature, reduces the residual alkali content, improves the magnification and low-temperature performance, and improves the overall performance of the positive electrode material .
Patent Information
- Application Number
- CN202310506362.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-05
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-05-05
AI Technical Summary
The methods used in the prior art for preparing single-crystal ternary materials have problems such as poor adaptability of the precursor, difficult to control the sintering temperature and performance, high residual alkali content, and poor magnification and low temperature performance.
By pre-firing and crushing the ternary precursor, a spherical oxide precursor is obtained and first sintered with lithium oxide and dopant under dry air or oxygen atmosphere, followed by nickel oxide under protective atmosphere , aluminum oxide and boron oxide are used to perform the second sintering to prepare a single-crystal ternary material, lithium oxide is used to replace lithium hydroxide and lithium carbonate to reduce the residual alkali content, and dopants are introduced to improve the rate performance.
The particle size of single-crystal ternary material is easily controlled, the residual alkali content is low, the magnification and low temperature performance are improved, the circulation and storage performance of the positive electrode material is improved, and the sintering temperature and performance are stabilized.
Smart Images

Figure CN116497450B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion positive electrode material preparation, and in particular, relates to a method for preparing a single crystal ternary material, a single crystal ternary material and a lithium ion battery. Background Art
[0002] As a most advanced energy conversion technology, lithium-ion batteries have been widely used in portable power tools, electric vehicles, energy storage power stations and other fields due to their advantages such as high energy density, safety, environmental protection, and long cycle. As one of the four main materials of lithium-ion batteries, the positive electrode material determines the energy density of lithium-ion batteries.
[0003] Lithium iron phosphate is the most common positive electrode material for lithium-ion batteries, but due to its small specific capacity (theoretical specific capacity 170mAh / g) and low discharge voltage platform (~3.45V), the energy density of the assembled battery is generally low. It is reported that in 2021, Guoxuan High-tech announced a lithium iron phosphate battery with a single cell energy density of 210Wh / kg, which is the lithium iron phosphate battery with the highest single cell energy density on the market. However, its energy density is only comparable to that of the ternary material NCM5 series. Therefore, in order to increase the energy density of batteries, major manufacturers have used ternary materials as positive electrode materials for lithium-ion batteries.
[0004] Most commercial ternary cathode materials are secondary spherical polycrystalline materials formed by the agglomeration of nanoscale primary particles. There are a large number of grain boundaries inside the polycrystalline NCM. During the battery charging and discharging process, due to the anisotropic lattice changes, polycrystalline NCM is prone to grain boundary cracking, resulting in secondary particle breakage, rapid increase in specific surface area and interface side reactions, resulting in increased battery impedance and rapid performance degradation. Single crystal ternary materials have no grain boundaries inside, which can effectively deal with the problem of grain boundary breakage and the performance degradation caused by it.
[0005] However, the methods used in the prior art to prepare single-crystal ternary materials have many shortcomings: 1) The precursor has poor adaptability. The sintering of single-crystal ternary materials requires the use of small-particle precursors, and the particle size requirements are relatively narrow; 2) The sintering temperature and performance of single-crystal ternary materials are not easy to control. The sintering temperature is low and the material capacity is high, but the material presents a small-particle polycrystalline morphology rather than a single-crystal morphology. The sintering temperature is high, and the material capacity is difficult to exert, and the material has a good single-crystal morphology; 3) The residual alkali content is high. Since the single-crystal ternary material will add more lithium hydroxide or lithium carbonate during the synthesis process to compensate for the volatilization of the lithium source due to the increase in temperature, more residual alkali will be present on the surface of the material; 4) The rate and low-temperature performance are poor. Since the primary particles of the single-crystal ternary material are larger, Li + The transmission distance is large, resulting in poor material rate and low temperature performance.
[0006] In view of the existence of the above problems, it is necessary to develop a method for preparing single crystal ternary materials that can take into account precursors of different particle sizes (including polycrystalline precursors and single crystal precursors), and the prepared single crystal particles have easy-to-control particle size, low residual alkali content, good rate and low-temperature performance. Summary of the invention
[0007] The main purpose of the present invention is to provide a method for preparing single crystal ternary materials, single crystal ternary materials and lithium ion batteries, so as to solve the problems existing in the prior art of the method for preparing single crystal ternary materials, such as poor precursor adaptability, difficulty in controlling the sintering temperature and performance of single crystal ternary materials, high residual alkali content, and poor rate and low temperature performance.
[0008] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a single crystal ternary material on the one hand, which comprises the following steps: pre-sintering and crushing a ternary precursor in sequence to obtain a quasi-spherical oxide precursor, the particle size of the quasi-spherical oxide precursor being: Dmin≥0.7μm, D10≥1.0μm, D50=2.0~5.0μm, D90≤13.0μm, Dmax≤20μm; in a dry air or oxygen atmosphere, subjecting the quasi-spherical oxide precursor, lithium oxide and a dopant to a first sintering process to obtain a single crystal ternary material intermediate; in a protective atmosphere, subjecting the single crystal ternary material intermediate, nickelous oxide, aluminum oxide and boric oxide to a second sintering process to obtain a single crystal ternary material.
[0009] Furthermore, the ternary precursor adopts the molecular formula Ni x A y M 1-x-y (OH)2 indicates that the single crystal ternary material adopts the molecular formula LiNi x A y M 1-x-y O2 represents, wherein A and M are selected from Co, Mn, B, Al, Zr, W, Ta, Nb, Ti, Fe, Y, Ga, Cu, Zn, Ge, Mo, V and Cr, and A and M are not the same, x≥0.50, 0≤y≤0.20, x+y≤1.0.
[0010] Furthermore, the pre-firing process includes: in a dry air or oxygen atmosphere, raising the temperature of the ternary precursor to a pre-firing temperature, sintering at a constant temperature, and then cooling to obtain a pre-sintered product; preferably, the pre-firing temperature is 700-1000°C.
[0011] Furthermore, the sintering temperature of the first sintering process is 700-1000° C., and the time is 8-24 hours.
[0012] Furthermore, the dopant is a high-valent metal element dopant with an oxidation valence state ≥ +5, preferably one or more of tungsten oxide, tantalum oxide, niobium oxide, rhenium oxide and vanadium oxide; preferably, the content of the metal element in the dopant relative to the spherical oxide precursor is 0.01% to 1% by weight.
[0013] Furthermore, the particle size of lithium oxide is D50=2.0-10.0 μm; the ratio of the sum of the molar number of Ni element, A element, and M element in the spherical oxide precursor to the molar number of lithium element in lithium oxide is 1:(0.95-1.09).
[0014] Furthermore, the method for preparing a single crystal ternary material also includes adding a low melting point lithium supplement agent having a melting point lower than that of lithium oxide in the first sintering process; preferably, the molar ratio of lithium oxide to the lithium element in the low melting point lithium supplement agent is 1:(0.01-0.1); preferably, the lithium supplement agent is one or more of lithium nitrate, lithium sulfate, lithium chloride, lithium sulfide, lithium fluoride, lithium bromide, lithium iodide, lithium sulfite, lithium hypochlorite and lithium perchlorate, and more preferably one or more of lithium nitrate, lithium sulfate and lithium fluoride.
[0015] Furthermore, the temperature of the second sintering process is 500-800°C; preferably, the protective atmosphere is one or more of nitrogen, helium, neon, argon, xenon or radon atmosphere; preferably, the particle size of nickelous oxide is D50=30-200nm; the particle size range of aluminum oxide is D50=30-100nm; the particle size of boron oxide is D50=0.1-2μm; preferably, relative to the single crystal ternary material intermediate, the coating amounts of nickelous oxide, aluminum oxide and boron oxide are 0.1-1%, 0.01-0.2% and 0.02-0.1% by weight, respectively.
[0016] In order to achieve the above-mentioned object, another aspect of the present invention further provides a single crystal ternary material, which is prepared by the above-mentioned preparation method.
[0017] Another aspect of the present invention provides a positive electrode material, which includes the above-mentioned single crystal ternary material.
[0018] Another aspect of the present invention provides a lithium-ion battery comprising the above-mentioned positive electrode material.
[0019] By applying the technical solution of the present invention, a quasi-spherical oxide precursor that meets the particle size requirements of a single crystal ternary material can be obtained after pre-sintering and crushing. This quasi-spherical oxide precursor has a morphology similar to that of a single crystal ternary material, and has fewer grain boundaries inside its particles, which is conducive to the rapid diffusion of lithium ions from lithium oxide to the inside of the oxide precursor to form a ternary material when mixed with lithium oxide for sintering. In addition, the quasi-spherical particle design helps the positive electrode material to slide quickly when the material pole piece is rolled, and the particles are in close contact, thereby improving the compaction density and rate performance. In addition, the quasi-spherical particle design can reduce the specific surface area of the material, reduce the side reactions between the particles and the electrolyte, and thus improve the material circulation and storage performance. Therefore, the above-mentioned precursor has universal applicability, and the sintering temperature and performance are relatively stable. The use of lithium oxide instead of conventional lithium hydroxide and / or lithium carbonate can avoid the presence of impurities such as hydroxide and carbonate that are easy to form alkaline substances, thereby reducing the residual lithium content in the single crystal ternary material. The introduction of dopants is conducive to improving the rate performance of the final single-crystal ternary material. The ternary precursor is first pre-sintered to obtain the particle size and morphology required by the single-crystal ternary material, and then the dopant is introduced for doping, which can reduce the risk of the dopant participating in the reaction in advance to form lithium compounds and coating the surface of the material to limit the particle growth and fail to reach the particle size required by the single-crystal ternary material. Nano nickel oxide and boron oxide coat the single-crystal ternary material intermediate at high temperature, and can react with residual alkali to generate lithium nickelate (Li2NiO2) and lithium borate, further consuming residual alkali, thereby effectively reducing the residual alkali content on the surface of the single-crystal ternary material. In summary, the use of the above method to prepare single-crystal ternary materials can greatly reduce their residual alkali content. In addition, lithium nickelate is a positive electrode pre-lithium material, which provides pre-lithium for graphite and / or silicon-carbon negative electrodes in the first charging stage of the full battery system, avoids excessive reversible lithium loss of the main material, stabilizes the material structure, and improves its cycle and storage performance. Lithium borate, as a fast ion conductor, is coated on the surface of ternary materials, which can improve the material's rate and low-temperature performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0021] Figure 1 This is a SEM image of the oxide precursor obtained after the ternary precursor in Example 1 is pre-sintered, crushed and reshaped;
[0022] Figure 2 The particle size distribution of lithium oxide obtained after pre-burning and crushing the lithium hydroxide in Example 1;
[0023] Figure 3 This is a SEM image of the finished single crystal ternary material obtained in Example 1;
[0024] Figure 4 This is a SEM image of the finished single crystal ternary material obtained in Comparative Example 1;
[0025] Figure 5 This is a SEM image of the finished single crystal ternary material obtained in Comparative Example 11;
[0026] Figure 6 This is a rate cycle performance diagram of a lithium-ion battery assembled from the single crystal ternary materials prepared in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0027] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0028] As described in the background technology, the methods used to prepare single crystal ternary materials in the prior art have the problems of poor precursor adaptability, difficulty in controlling the sintering temperature and performance of single crystal ternary materials, high residual alkali content, and poor rate and low temperature performance. In order to solve the above technical problems, the present application provides a method for preparing single crystal ternary materials, comprising the following steps: pre-calcining and crushing the ternary precursor in sequence to obtain a quasi-spherical oxide precursor, the particle size of the quasi-spherical oxide precursor is: Dmin≥0.7μm, D10≥1.0μm, D50=2.0~5.0μm, D90≤13.0μm, Dmax≤20μm; in dry air or oxygen atmosphere, subjecting the quasi-spherical oxide precursor, lithium oxide and dopant to a first sintering process to obtain a single crystal ternary material intermediate; in a protective atmosphere, subjecting the single crystal ternary material intermediate, nickelous oxide, aluminum oxide and boric oxide to a second sintering process to obtain the single crystal ternary material.
[0029] Wherein, D10, D50 and D90 refer to the particle sizes corresponding to the cumulative particle size distribution percentages of the sample of 10%, 50% and 90% respectively. Dmin and Dmax refer to the minimum and maximum particle sizes of the sample respectively.
[0030] After pre-sintering and crushing, a quasi-spherical oxide precursor that meets the particle size requirements of single-crystal ternary materials can be obtained. This type of spherical oxide precursor has a similar morphology to single-crystal ternary materials, and its particles have fewer grain boundaries, which is conducive to the rapid diffusion of lithium ions from lithium oxide to the oxide precursor to form ternary materials when mixed with lithium oxide for sintering. In addition, the quasi-spherical particle design helps the positive electrode material to slide quickly when the material pole piece is rolled, and the particles are in close contact, thereby improving the compaction density and rate performance. In addition, the quasi-spherical particle design can reduce the specific surface area of the material and reduce the side reactions between the particles and the electrolyte, thereby improving the material circulation and storage performance. Therefore, the above-mentioned precursor is universal, and the sintering temperature and performance are relatively stable. The use of lithium oxide instead of conventional lithium hydroxide and / or lithium carbonate can avoid the presence of impurities such as hydroxide and carbonate that are easy to form alkaline substances, thereby reducing the residual lithium content in single-crystal ternary materials. The introduction of dopants is beneficial to improving the rate performance of the final single-crystal ternary material. The ternary precursor is first pre-sintered to obtain the particle size and morphology required by the single-crystal ternary material, and then the dopant is introduced. This can reduce the risk of the dopant participating in the reaction in advance to form lithium compounds and coating the surface of the material to limit particle growth and fail to reach the particle size required by the single-crystal ternary material. Nano-nickel oxide and boron oxide coat the single-crystal ternary material intermediate at high temperature, and can react with residual alkali to generate lithium nickelate (Li2NiO2) and lithium borate, further consuming residual alkali, thereby effectively reducing the residual alkali content on the surface of the single-crystal ternary material. Alumina coating can reduce the active sites on the surface of the material, reduce side reactions with the electrolyte, and improve the material's circulation and storage performance. In summary, the preparation of single-crystal ternary materials using the above method can greatly reduce their residual alkali content. In addition, lithium nickel oxide is a positive electrode pre-lithium material, which provides pre-lithium for graphite and / or silicon-carbon negative electrodes during the first charging stage of the full battery system, avoiding excessive reversible lithium loss in the main material, stabilizing the material structure, and improving its cycle and storage performance. Lithium borate is a fast ion conductor, which is coated on the surface of the ternary material and can improve the material rate and low-temperature performance.
[0031] The ternary precursor used in the above method is a conventional precursor substance used in the art for synthesizing single crystal ternary materials. Specifically, the ternary precursor can be a hydroxide synthesized in a conventional coprecipitation process. In a preferred embodiment, the ternary precursor is a precursor of the molecular formula Ni x A y M 1-x-y (OH)2 represents that the single crystal ternary material adopts the molecular formula LiNi x A y M 1-x-yO2 represents, wherein A and M are selected from Co, Mn, B, Al, Zr, W, Ta, Nb, Ti, Fe, Y, Ga, Cu, Zn, Ge, Mo, V and Cr, and A and M are different, x ≥ 0.50, 0 ≤ y ≤ 0.20, x + y ≤ 1.0. For example, the ternary precursor can be Ni 0.80 Co 0.10 Mn 0.10 (OH)2 or Ni 0.80 Co 0.15 Al 0.05 (OH)2. The selection of ternary precursors is not limited to the above substances, but the selection of the above substances is more conducive to obtaining single crystal ternary materials with good performance. The particle size of the ternary precursor is not particularly limited. The small particle (D50 range 2 to 5 μm) and large particle (D50 range 7 to 12 μm) precursors prepared by conventional intermittent and continuous methods in the art can be used to synthesize single crystal ternary materials using the method of the present invention.
[0032] The above-mentioned pre-firing process is an aerobic sintering process, which can be implemented using the commonly used devices and processes in this field. In a preferred embodiment, the above-mentioned pre-firing process includes: in a dry air or oxygen atmosphere, the ternary precursor is raised to the pre-firing temperature, and then constant temperature sintering is performed, and then cooling is performed to obtain a pre-sintered product. As mentioned above, by first pre-firing the ternary precursor to obtain the particle size and morphology required for the single crystal ternary material, and then performing subsequent treatment, it is beneficial to obtain the particle size and morphology required for the single crystal ternary material, and improve the adaptability of the method to the precursor. Preferably, the pre-firing temperature of the ternary precursor is 700-1000°C, and the time is 4-6h.
[0033] In a preferred embodiment, the crushing treatment of the ternary precursor after pre-sintering includes the oxide precursor obtained by pre-sintering being initially crushed by a rotary mill, and then further crushed by a jet mill, the crushed oxide precursor is mixed with an organic liquid to prepare a slurry, the slurry is transferred to a ball mill for ball milling and shaping, and finally vacuum dried to obtain the shaped oxide precursor. The crushing and shaping of the oxide precursor are conducive to obtaining an oxide precursor with a desired particle size and morphology. In a preferred embodiment, the oxide precursor is mixed with an organic solution in a mass ratio of 1.0:0.1 to 1.0 to prepare a slurry, and the organic solution is one or more of methanol, ethanol, n-propanol, isopropanol, ethylene glycol, NMP and polydimethylsiloxane. In a preferred embodiment, in the above-mentioned shaping, the oxide precursor and the grinding balls are mixed in a mass ratio (dry weight) of 1:0.3-10, preferably 1:0.5-2; preferably, the particle size of the grinding balls is 0.05-10 mm, preferably 0.05-2 mm; preferably, the material of the grinding balls is one or both of zirconium oxide and agate; preferably, the ball milling rate of the ball mill is 50-200 r / min, preferably 80-150 r / min; preferably, the ball milling time is 1-10 h, preferably 4-8 h.
[0034] A single crystal ternary material intermediate, i.e., an uncoated single crystal ternary material, is obtained through the first sintering process. In a preferred embodiment, the temperature of the first sintering treatment process is 700-1000°C, and the sintering time is 8-24h. The temperature and sintering time of the first sintering treatment include but are not limited to the above ranges, and limiting them within the above ranges is beneficial to further improve the performance of the obtained ternary single crystal material. The first sintering treatment is carried out in dry air or oxygen atmosphere. The lithium oxide used in the first sintering process can be obtained by methods commonly used in the art. Calcining lithium hydroxide or lithium carbonate to form lithium oxide as a lithium source can reduce the presence of hydroxide, water molecules and carbonate in the lithium source, and effectively reduce the residual alkali content of the ternary material.
[0035] In the above preparation method, the dopant can be selected from the types commonly used in the art. In a preferred embodiment, the dopant is a high-valent metal element dopant with an oxidation valence state ≥ +5, preferably one or more of tungsten oxide, tantalum oxide, niobium oxide, rhenium oxide and vanadium oxide; preferably, the content of the metal element in the dopant relative to the spherical oxide precursor is 0.01% to 1% by weight. By introducing high-valent metal element doping during the single crystal synthesis process, the rate and low-temperature performance of the single crystal ternary material can be improved. Specifically, the high-valent metal ions and Ni 3+ The radius is similar, and it can be doped into the transition metal layer of the ternary material, reducing the average valence state of Ni through the charge compensation mechanism, thereby reducing the lithium ion diffusion barrier, improving the diffusion kinetics, and improving the rate and low-temperature performance of the single crystal ternary material.
[0036] In a preferred embodiment, the particle size of lithium oxide is D50=2.0~10.0 μm, and the ratio of the sum of the molar numbers of Ni element, A element and M element in the spherical oxide precursor to the molar number of lithium element in the lithium oxide is 1:(0.95~1.09).
[0037] In a preferred embodiment, the preparation method further comprises adding a low melting point lithium supplement agent having a melting point lower than that of lithium oxide during the first sintering process. Using the lithium supplement agent and lithium oxide together as a lithium source helps to reduce the residual alkali content of the ternary material. The lithium supplement agent is a low melting point lithium-containing compound having a melting point lower than that of lithium oxide, and its addition can reduce the synthesis temperature of the single crystal ternary material. Preferably, the molar ratio of the lithium oxide to the lithium element in the low melting point lithium supplement agent is 1:(0.01-0.1). Preferably, the lithium supplement agent is one or more of lithium nitrate (melting point 264°C), lithium sulfate (melting point 859°C), lithium chloride (melting point 605°C), lithium sulfide (melting point 938°C), lithium fluoride (melting point 845°C), lithium bromide (melting point 442-527°C), lithium iodide (melting point 446°C), lithium sulfite (melting point 455°C), lithium hypochlorite (melting point 100°C) and lithium perchlorate (melting point 236°C), more preferably one or more of lithium nitrate, lithium sulfate and lithium fluoride.
[0038] The coated single crystal ternary material can be obtained through the second sintering process. In a preferred embodiment, the temperature of the second sintering process is 500-800°C. As described above, the single crystal ternary material is mixed with nickel oxide, aluminum oxide and boron oxide, and sintered at high temperature in a protective atmosphere. The protective atmosphere is a mixed gas atmosphere of one or more of nitrogen, helium, neon, argon, xenon or radon. The surface residual alkali reacts with nickel oxide and boron oxide to form lithium nickelate (Li2NiO2) and lithium borate. Lithium nickelate is a positive electrode pre-lithium material. In the first charging stage of the full battery system, it provides pre-lithium for graphite and / or silicon-carbon negative electrodes, avoids excessive reversible lithium loss of the main material, stabilizes the material structure, and improves its cycle and storage performance. As a fast ion conductor, lithium borate is coated on the surface of the ternary material, which can improve the material rate and low temperature performance. Alumina coating can reduce the active sites on the surface of the material, reduce side reactions with the electrolyte, and improve the material cycle and storage performance. By using lithium oxide and lithium supplement as lithium sources, and then subjecting to high temperature coating treatment in the later stage, the residual alkali content can be reduced to an extremely low level (free lithium content ≤ 1000ppm), achieving an effect equivalent to water washing. In a preferred embodiment, the particle size of the nickelous oxide is D50 = 30-200nm; the particle size range of the aluminum oxide is D50 = 30-100nm; the particle size of the boric oxide is D50 = 0.1-2μm. In a preferred embodiment, relative to the single crystal ternary material intermediate, the coating amounts of the nickelous oxide, the aluminum oxide and the boric oxide are 0.1-1%, 0.01-0.2% and 0.02-0.1% by weight, respectively.
[0039] Lithium oxide can be commercially available or prepared by itself. In a preferred embodiment, lithium oxide is prepared by the following method: lithium hydroxide or lithium carbonate, a lithium source, is weighed and placed in a protective atmosphere, heated to a preset calcination temperature, kept warm for 4 to 6 hours, cooled naturally to room temperature, air flow crushed, ball milled, and lithium oxide of suitable particle size is obtained.
[0040] Another aspect of the present application provides a single crystal ternary material, which is prepared by the above-mentioned preparation method.
[0041] By adopting the above preparation method, a quasi-spherical oxide precursor that meets the particle size requirements of the single crystal ternary material can be obtained after pre-sintering and crushing. This quasi-spherical oxide precursor has a similar morphology to the single crystal ternary material, and its particles have fewer grain boundaries, which is conducive to the rapid diffusion of lithium ions from lithium oxide to the oxide precursor to form a ternary material when mixed with lithium oxide for sintering. In addition, the quasi-spherical particle design helps the positive electrode material to slide quickly when the material pole piece is rolled, and the particles are in close contact, thereby improving the compaction density and rate performance. In addition, the quasi-spherical particle design can reduce the specific surface area of the material, reduce the side reactions between the particles and the electrolyte, and thus improve the material circulation and storage performance. Therefore, the above precursor is universal, and the sintering temperature and performance are relatively stable. The use of lithium oxide instead of conventional lithium hydroxide and / or lithium carbonate can avoid the presence of impurities such as hydroxide and carbonate that are easy to form alkaline substances, thereby reducing the residual lithium content in the single crystal ternary material. The introduction of dopants is beneficial to improving the rate performance of the final single crystal ternary material. The ternary precursor is first pre-sintered to obtain the particle size and morphology required by the single crystal ternary material, and then the dopant is introduced. This can reduce the risk of the dopant participating in the reaction in advance to form lithium compounds and coating the material surface to limit particle growth and fail to reach the particle size required by the single crystal ternary material. Nano nickel oxide and boron oxide coat the single crystal ternary material intermediate at high temperature, and can react with residual alkali to generate lithium nickelate (Li2NiO2), lithium borate and lithium aluminate, further consuming residual alkali, thereby effectively reducing the residual alkali content on the surface of the single crystal ternary material. In summary, the single crystal ternary material prepared by the above method can greatly reduce the amount of residual alkali.
[0042] Another aspect of the present application provides a positive electrode material, including the above-mentioned single crystal ternary material.
[0043] Another aspect of the present application provides a lithium-ion battery comprising the above-mentioned positive electrode material.
[0044] The single crystal ternary material provided in the present application has the advantages of structural stability, good cycle and storage performance, rate and low temperature performance, etc. Therefore, the positive electrode material and lithium-ion battery prepared therefrom can improve structural stability, cycle and storage performance, as well as rate and low temperature performance.
[0045] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0046] Example 1
[0047] 50kg of ternary precursor Ni 0.80 Co 0.10 Mn 0.10(OH)2 was placed in a box-type atmosphere furnace, dry air was introduced, and then heating was started. The temperature was raised to 850℃ at a rate of 5℃ / min, kept at this temperature for 10h, and then naturally cooled to room temperature to obtain Ni 0.80 Co 0.10 Mn 0.10 O x The oxide precursor Ni is milled by rotary wheel milling. 0.80 Co 0.10 Mn 0.10 O x After the initial crushing, the oxide precursor is further crushed by jet mill to obtain an oxide precursor with a particle size range of Dmin≥0.7μm, D10≥1.0μm, D50=2.5~4.0μm, D90≤9.0μm, Dmax≤12.0μm (see Figure 2 ). The crushed oxide precursor and ethanol were mixed in a mass ratio of 1:0.5 and transferred to a ball mill. Zirconia balls with a diameter of 1 mm were added in an amount of 1.3 times the mass of the oxide precursor. The ball mill speed was controlled to be 80 r / min and the ball milling time was 4 h. After the ball milling was completed, the grinding balls were separated from the ball milling slurry through a 100-mesh sieve, and then the ball milling slurry was placed in a vacuum oven at 80°C and heated for 12 h, and then crushed again using a mortar mill and passed through a 350-mesh vibrating sieve.
[0048] 30 kg of battery-grade lithium hydroxide monohydrate was placed in a box-type atmosphere furnace, nitrogen protective gas was introduced, the gas flow rate was controlled at 10 L / min, the temperature was increased to 600 ° C at a heating rate of 2 ° C / min, and the mixture was kept warm for 10 hours, then naturally cooled to room temperature, and then crushed by air flow mill and ball mill to obtain lithium oxide with a particle size D50 of about 5 μm.
[0049] The Ni 0.80 Co 0.10 Mn 0.10 O x The oxide precursor and the crushed lithium oxide are mixed at a molar ratio of 1:1.04 of the sum of the molar numbers of Ni element, A element, M element and lithium oxide in the oxide precursor, and then lithium nitrate as a lithium supplement and tantalum oxide as a dopant are added, the amount of lithium nitrate is 5% mol of the element lithium in the lithium oxide, and tantalum oxide is added with the mass of tantalum element being 0.4% of the mass of the oxide precursor, and then placed in a box-type atmosphere furnace, industrial oxygen is introduced, and the temperature is increased to 850°C at a heating rate of 2°C / min, and the temperature is kept for 10 hours, and then naturally cooled to room temperature, and crushed by a stone mortar and passed through a 350-mesh vibrating sieve to obtain LiNi 0.8 Co 0.1 Mn 0.1 O2 single crystal ternary material.
[0050] Press LiNi 0.8Co 0.1 Mn 0.1 0.35%, 0.1% and 0.05% of the mass of O2 single crystal ternary material are mixed with nickel oxide, aluminum oxide and boron oxide, respectively. The particle size D50 of nickel oxide is 100nm, the particle size D50 of aluminum oxide is 50nm, and the particle size D50 of boron oxide is about 1μm. The mixed material is placed in a box atmosphere furnace, nitrogen is introduced, and the temperature is increased to 600℃ at a rate of 5℃ / min, and kept at this temperature for 5h, and then naturally cooled to room temperature to obtain modified LiNi 0.8 Co 0.1 Mn 0.1 O2 single crystal ternary material.
[0051] Comparative Example 1
[0052] The difference from Example 1 is that the ternary precursor Ni 0.80 Co 0.10 Mn 0.10 (OH)2 is not pre-burned or crushed.
[0053] Comparative Example 2
[0054] The difference from Comparative Example 1 is that the lithium oxide in Comparative Example 1 is replaced with lithium hydroxide of the same particle size.
[0055] Comparative Example 3
[0056] The difference from Example 1 is that the particle size of lithium oxide in Example 1 is controlled to D50=1 μm.
[0057] Comparative Example 4
[0058] The difference from Example 1 is that the particle size of lithium oxide in Example 1 is controlled to D50=15 μm.
[0059] Comparative Example 5
[0060] The difference from Example 1 is that the Ni 0.80 Co 0.10 Mn 0.10 O x The oxide precursor and the crushed lithium oxide are mixed at a molar ratio of 1:0.93 of the sum of the molar numbers of the Ni element, the A element, the M element and the lithium oxide in the oxide precursor.
[0061] Comparative Example 6
[0062] The difference from Example 1 is that the Ni 0.80 Co 0.10 Mn 0.10 O xThe oxide precursor and the crushed lithium oxide are mixed at a molar ratio of 1:1.12 of the sum of the molar numbers of the Ni element, the A element, the M element and the lithium oxide in the oxide precursor.
[0063] Comparative Example 7
[0064] The difference from Example 1 is that the lithium supplement agent in Example 1 is removed.
[0065] Comparative Example 8
[0066] The difference from Example 1 is that the amount of the lithium supplement in Example 1 is increased to 20 mol%.
[0067] Comparative Example 9
[0068] The difference from Example 1 is that no dopant is used.
[0069] Comparative Example 10
[0070] The difference from Example 1 is that the oxide precursor obtained after pre-calcination is initially crushed by a rotary mill and further crushed by a jet mill without being shaped.
[0071] Example 2
[0072] The difference from Example 1 is that the dopant in Example 1 is replaced with tungsten oxide, and the doping amount is changed to 0.2%.
[0073] Example 3
[0074] 50kg of ternary precursor Ni 0.92 Co 0.06 Mn 0.02 (OH)2 was placed in a box-type atmosphere furnace, dry air was introduced, and then heating was started. The temperature was raised to 810℃ at a rate of 5℃ / min, kept at this temperature for 10h, and then naturally cooled to room temperature to obtain Ni 0.92 Co 0.06 Mn 0.02 O x The oxide precursor Ni is milled by rotary wheel milling. 0.92 Co 0.06 Mn 0.02 O xAfter the initial crushing, the oxide precursor is further crushed by a jet mill to obtain an oxide precursor with a particle size range of Dmin≥0.7μm, D10≥1.0μm, D50=2.5~4.0μm, D90≤9.0μm, and Dmax≤12.0μm. The crushed oxide precursor is mixed with ethanol in a mass ratio of 1:0.3 and transferred to a ball mill, and zirconium oxide balls with a diameter of 1mm are added in an amount of 1.3 times the mass of the oxide precursor. The ball mill speed is controlled to be 80r / min and the ball milling time is 4h. After the ball milling is completed, the grinding balls are separated from the ball milling slurry through a 100-mesh sieve, and then the ball milling slurry is placed in a vacuum oven at 80℃ and heated for 12h, and then crushed again using a mortar mill and passed through a 350-mesh vibrating sieve.
[0075] 30 kg of battery-grade lithium hydroxide monohydrate was placed in a box-type atmosphere furnace, nitrogen protective gas was introduced, the gas flow rate was controlled at 10 L / min, the temperature was increased to 600 ° C at a heating rate of 2 ° C / min, and the mixture was kept warm for 10 hours, then naturally cooled to room temperature, and then crushed by air jet mill and ball mill to obtain lithium oxide with a particle size of D50 of about 5 μm.
[0076] The Ni 0.92 Co 0.06 Mn 0.02 O x The oxide precursor and the crushed lithium oxide are mixed at a molar ratio of 1:1.01 of the sum of the molar numbers of Ni element, A element, M element and lithium oxide in the oxide precursor, and then lithium fluoride as a lithium supplement and tantalum oxide as a dopant are added, the amount of lithium fluoride is 8% mol of the elemental lithium in the lithium oxide, and tantalum oxide is added with the mass of tantalum element being 4000ppm of the mass of the oxide precursor, and then placed in a box-type atmosphere furnace, industrial oxygen is introduced, and the temperature is increased to 800°C at a heating rate of 2°C / min, kept warm for 10 hours, and then naturally cooled to room temperature, crushed by a stone mortar mill and passed through a 350-mesh vibrating sieve to obtain LiNi 0.92 Co 0.06 Mn 0.02 O2 single crystal ternary material.
[0077] Press LiNi 0.92 Co 0.06 Mn 0.02 0.5%, 0.15% and 0.05% of the mass of O2 single crystal ternary material are mixed with nickel oxide, aluminum oxide and boron oxide, respectively. The particle size D50 of nickel oxide is 100nm, the particle size D50 of aluminum oxide is 50nm, and the particle size D50 of boron oxide is about 1μm. The mixed material is placed in a box atmosphere furnace, nitrogen is introduced, and the temperature is increased to 600℃ at a rate of 5℃ / min, and kept at this temperature for 5h, and then naturally cooled to room temperature to obtain modified LiNi 0.92 Co 0.06 Mn0.02 O2 single crystal ternary material.
[0078] Comparative Example 11
[0079] The difference from Example 3 is that the nickel oxide coating in Example 3 is removed.
[0080] Comparative Example 12
[0081] The difference from Implementation 3 is that the alumina coating in Implementation 3 is removed.
[0082] Comparative Example 13
[0083] The difference from Example 3 is that all the coatings in Example 3 are removed.
[0084] The oxide precursor obtained after pre-sintering, crushing and shaping of the ternary precursor in Example 1 and the finished single crystal ternary material were characterized by scanning electron microscopy. The results are as follows: Figure 1 and Figure 3 As shown, through Figure 1 and Figure 3 It can be observed that the oxide precursor has a similar morphology to the finished ternary material, both of which have rounded particle surfaces and are spherical or quasi-spherical.
[0085] In addition, the single crystal ternary materials in Comparative Examples 1 and 10 were characterized by scanning electron microscopy. Figure 4 and 5 As shown in the figure, the material particles are irregular and have sharp edges and corners, indicating that the morphology of the single crystal material prepared after shaping is quite different from that of the single crystal material prepared without shaping. Figure 5 Material retention and Figure 1 Similar primary particle size, Figure 4 It is smaller than the previous two, indicating that pre-burning of the precursor can inhibit the restriction on the growth of single crystal ternary material grain size caused by the introduction of dopants.
[0086] The single crystal ternary materials of Examples 1 to 3 and Comparative Examples 1 to 13 were characterized by XRD, and the obtained XRD was refined by XRD refinement software GASS to obtain the lithium nickel mixing ratio (Ni 2+ / Li + % mol).
[0087] The single crystal ternary materials in Examples 1 to 3 and Comparative Examples 1 to 13 were respectively tested for residual alkali content according to the following residual alkali test method. The specific test steps are as follows, and the test results are shown in Table 1.
[0088] (1) Prepare 0.01 M standard hydrochloric acid solution: accurately weigh 0.0220 g of dried sodium carbonate (d) into a 250 mL volumetric flask, add 100 mL of deionized water, mix well, add 3 drops of methyl orange indicator, and titrate with hydrochloric acid (a) until the color changes from yellow to orange. Record the volume of hydrochloric acid consumed in the titration, and repeat the above steps twice.
[0089] (2) Sample preparation: Accurately weigh 5 g of the sample to be tested into a 250 mL conical flask, add 100 mL of deionized water, cover the flask with a stopper and shake for half an hour, dry filter, and set aside the filtrate;
[0090] (3) Determination of total alkalinity: Transfer 10 mL of the filtrate to a 250 mL conical flask, add 2 drops of methyl red-methylene blue (c), and titrate with standard hydrochloric acid solution (a) under constant shaking until the end point changes from green to reddish purple. Record the volume of hydrochloric acid consumed. The total volume of hydrochloric acid consumed by carbonate and hydroxide is V1.
[0091] (4) Determination of hydroxide: Pipette 10 mL of the filtrate into a 250 mL conical flask and add 5 mL of barium chloride (e) to precipitate carbonate and sulfate. Then add 2 drops of phenolphthalein indicator. If the filtrate turns red, it means that the filtrate contains hydroxide. If it does not turn red, it means that no hydroxide is present. Titrate with standard hydrochloric acid solution (a) under sufficient shaking until the red color disappears. Record the volume of hydrochloric acid consumed (V2).
[0092] (5) Calculation of analysis results:
[0093] The content of LiOH and Li2CO3 is calculated according to the following formula:
[0094]
[0095]
[0096] Where: V1 is the volume of hydrochloric acid consumed in titrating the total alkalinity (mL), V2 is the volume of hydrochloric acid consumed in titrating the hydroxide (mL), V3 is the volume of the filtrate taken for the determination of hydroxide (mL), m is the sample weight (g), and C is the concentration of hydrochloric acid (moL / L).
[0097] The single crystal ternary materials in Examples 1 to 3 and Comparative Examples 1 to 13, the conductive agent SP, and the binder PVDF were respectively prepared in a mass ratio of 97.5:1:1.5 using NMP as a solvent, coated on a carbon-coated aluminum foil, dried at 100°C for 5 hours, and compacted on a roller press to obtain a positive electrode sheet. A circular positive electrode sheet with a diameter of 12 mm was punched out using a sheet puncher, and the weight of the circular positive electrode was weighed m1, and the thickness of the positive electrode sheet was measured h1 using a micrometer. At the same time, a circular carbon-coated aluminum foil with a diameter of 12 mm was punched out, and the weight and thickness were weighed, marked m2 and h2 respectively.
[0098] The compaction density of button cell pole piece is calculated as follows:
[0099]
[0100] Where: m1 is the mass of the positive electrode of the disc (mg), h1 is the thickness of the positive electrode of the disc (μm), m2 is the mass of the carbon-coated foil of the disc (mg), and h2 is the thickness of the carbon-coated foil of the disc (μm).
[0101] With lithium metal sheet as negative electrode, 1M LiPF6 solution as electrolyte, cell gard2300 as separator, and the above positive electrode sheets were assembled into button cells, and charged and discharged at a rate of 0.2C within the cut-off voltage range of 2.8-4.35V, and then charged and discharged at 1C for 50 cycles, and the 0.2C charge and discharge specific capacity and 1C discharge specific capacity of the battery were measured. The first efficiency is the ratio of the first 0.2C discharge specific capacity to the 0.2C charge specific capacity.
[0102] -25℃ low temperature DCIR test is also an enterprise test method. The specific test steps are as follows:
[0103] (1) The button-type battery was assembled with the circular positive electrode sheet prepared above, and charged and discharged at 0.33C to obtain a 0.33C discharge capacity C1, and then charged at a rate of 0.33C to a capacity of 20% of C1;
[0104] (2) Then place the button battery in a low-temperature cabinet at -25°C and use a charge and discharge test cabinet to collect voltage. First, let it stand for 30 minutes. After standing, the voltage is V1. Then, discharge at a rate of 0.33C for 18 seconds. The end voltage is V2. The 0.33C rate discharge current is recorded as I1.
[0105] (3) Calculate the -25℃ low temperature DCIR according to the following formula:
[0106]
[0107] Where: V1 is the voltage of the button battery after standing at 25°C for 30 minutes (V), V2 is the end voltage of the button battery at 0.33C rate discharge for 18 seconds (V), and I1 is the 0.33C rate discharge current (mA).
[0108] The test results of the buckling performance, electrode compaction density and low-temperature DCIR of the single crystal ternary materials in Examples 1 to 3 and Comparative Examples 1 to 13 are shown in Table 1.
[0109] The single crystal ternary material in Example 3 and Comparative Example 5, the conductive agent CNTs, and the binder PVDF were mixed in a mass ratio of 98:1:1, with NMP as the solvent, and the solid content was controlled to 70%. Then, the slurry was coated on the current collector aluminum foil, and the single surface density was controlled to 215g / m2 After rolling, the compaction density of the pole piece is 3.60g / cm 3 . According to the NP ratio of 1.13, it is matched with the silicon-carbon negative electrode, 1M LiPF6 solution is used as the electrolyte, Cellgard2300 is used as the separator, and a 3Ah soft pack battery is assembled. After formation, 0.33C and 1C are charged and discharged twice to obtain 0.33C and 1C gram capacities. The ratio of the first 0.33C discharge capacity to the sum of the charge capacity in the formation stage plus the first 0.33C charge capacity is the first efficiency of the 3Ah soft pack. The electrochemical properties of the product are shown in Table 1.
[0110] Table 1 Residual alkali content, pole piece compaction density and electrochemical performance test of lithium ion battery in the examples and comparative examples
[0111]
[0112]
[0113] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0114] Comparison of Examples 1-2 with Comparative Examples 1-10 and Example 3 with Comparative Examples 11-13 shows that the single crystal ternary material prepared by the method provided in the present application has a more excellent charge and discharge capacity, cycle performance, and lower low temperature resistance and residual alkali content. For example, see Figure 1 It can be seen that the battery prepared in Example 1 has improved capacity and cycle performance compared with Comparative Example 1.
[0115] By comparing Example 1 with Comparative Examples 1 and 10, it can be seen that the preferred shaping steps of the present application are beneficial to improving the charge and discharge capacity, initial efficiency, pole piece compaction density, and low-temperature resistance of the single crystal ternary material.
[0116] By comparing Comparative Example 1 with Comparative Example 2, it can be seen that using lithium oxide as a lithium source can effectively reduce the residual alkali content of the single crystal ternary material.
[0117] Comparing Example 1 with Comparative Examples 3-4, 5-6, 7-8, it can be seen that the preferred lithium oxide particle size, ratio of lithium oxide to oxide precursor, and amount of lithium supplement added in the present application are beneficial to reducing the lithium-nickel mixing of single crystal ternary materials, reducing the residual alkali content, increasing the discharge capacity, improving the cycle performance, and reducing the low-temperature DCIR. In addition, for Comparative Example 3, the smaller lithium oxide particle size relative to the preferred range of the present application also increases the processing cost; for Comparative Example 5, although reducing the amount of lithium oxide reduces the residual alkali, it significantly aggravates the lithium-nickel mixing, and the battery performance is poor.
[0118] By comparing Example 1 with Comparative Example 9, it can be seen that the use of the preferred doping amount of the dopant in the present application is beneficial to improving the rate performance and reducing the low-temperature DCIR.
[0119] Comparing Example 3 with Comparative Examples 11 to 13, it can be seen that the use of nickel oxide and boron oxide is beneficial to reducing the residual alkali content, and the use of aluminum oxide coating is beneficial to improving the rate performance and reducing the low-temperature DCIR.
[0120] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0121] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a single crystal ternary material, characterized in that: The method comprises the following steps: The ternary precursor is pre-calcined and crushed in sequence to obtain a quasi-spherical oxide precursor, wherein the particle size of the quasi-spherical oxide precursor is: Dmin≥0.7μm, D10≥1.0μm, D50=2.0~5.0μm, D90≤13.0μm, Dmax≤20μm; Under dry air or oxygen atmosphere, subjecting the quasi-spherical oxide precursor, lithium oxide and dopant to a first sintering process to obtain a single crystal ternary material intermediate; Under a protective atmosphere, subjecting the single crystal ternary material intermediate, nickelous oxide, aluminum oxide and boron oxide to a second sintering process to obtain the single crystal ternary material; The method for preparing a single crystal ternary material further comprises adding a low melting point lithium supplementing agent having a melting point lower than that of lithium oxide during the first sintering process; The molar ratio of the lithium oxide to the lithium element in the low melting point lithium supplement is 1:(0.01-0.1); The lithium supplement agent is one or more of lithium nitrate, lithium sulfate, lithium chloride, lithium sulfide, lithium fluoride, lithium bromide, lithium iodide, lithium sulfite, lithium hypochlorite and lithium perchlorate; The dopant is a high-valent metal element dopant with an oxidation valence state of ≥+5.
2. The method according to claim 1, characterized in that: The ternary precursor adopts the molecular formula Ni x A y M 1-x-y (OH)2 represents that the single crystal ternary material adopts the molecular formula LiNi x A y M 1-x-y O2 represents, wherein A and M are selected from Co, Mn, B, Al, Zr, W, Ta, Nb, Ti, Fe, Y, Ga, Cu, Zn, Ge, Mo, V and Cr, and A and M are not the same, x≥0.50, 0≤y≤0.20, x+y≤1.
0.
3. The method according to claim 1, characterized in that The pre-sintering comprises: raising the temperature of the ternary precursor to the pre-sintering temperature in a dry air or oxygen atmosphere, sintering at a constant temperature, and then cooling to obtain a pre-sintered product.
4. The method according to claim 3, characterized in that The pre-firing temperature is 700-1000°C.
5. The method according to claim 1, characterized in that The sintering temperature of the first sintering process is 700-1000° C., and the time is 8-24 hours.
6. The method according to claim 1, characterized in that The dopant is one or more of tungsten oxide, tantalum oxide, niobium oxide, rhenium oxide and vanadium oxide. 7 . The method according to claim 6 , wherein the content of the metal element in the dopant relative to the spherical oxide precursor is 0.01% to 1% by weight.
8. The method according to claim 1, characterized in that The particle size of the lithium oxide is D50=2.0-10.0 μm; The ratio of the sum of the molar numbers of the Ni element, the A element and the M element in the quasi-spherical oxide precursor to the molar number of the lithium element in the lithium oxide is 1:(0.95-1.09).
9. The method according to claim 1, characterized in that: The lithium supplement agent is one or more of lithium nitrate, lithium sulfate and lithium fluoride.
10. The method according to claim 1, characterized in that The temperature of the second sintering process is 500-800°C.
11. The method according to claim 10, characterized in that The protective atmosphere is one or more of nitrogen, helium, neon, argon, xenon or radon atmosphere.
12. The method according to claim 10, characterized in that The particle size of the nickelous oxide is D50=30-200 nm; the particle size of the aluminum oxide is D50=30-100 nm; and the particle size of the boron oxide is D50=0.1-2 μm.
13. The method according to claim 10, characterized in that Relative to the single crystal ternary material intermediate, the coating amounts of the nickelous oxide, the aluminum oxide and the boron oxide are 0.1-1%, 0.01-0.2% and 0.02-0.1% by weight, respectively.
14. A single crystal ternary material, characterized in that: The single crystal ternary material is prepared by the method described in any one of claims 1 to 13.
15. A positive electrode material, characterized in that: The positive electrode material includes the single crystal ternary material according to claim 14.
16. A lithium ion battery comprising a positive electrode material, characterized in that: The positive electrode material is the positive electrode material according to claim 15.
Citation Information
Patent Citations
Surface-coated doped lithium manganate spherical secondary particles as well as preparation method and application thereof
CN109817900A
Positive electrode material preparation method and prepared positive electrode material
CN110518209A
Ternary positive electrode material of high-nickel monocrystal-like lithium ion battery and preparation method thereof
CN110931768A
Nickel-cobalt-manganese ternary positive electrode material and preparation method and application thereof
CN112499695A
Micron-sized lithium ion battery positive electrode material and preparation method thereof
CN114162879A
